Peculiarities of Expression of Leadership of Pre-Primary Children in Musical Activities - Rauduvaitė, Asta; Virganavičienė, Živilė (Pedagogika, 2015)
On the basis of scientific literature analysis it can be stated that at pre-primary age leadership is fostered developing children’s self-confidence, initiative, communication with adults, empathy, curiosity, leading of activities and play, activity, self-regulation and self-control, creativity, generating of ideas, which may be expressed in musical activities as well. Therefore, applying musical activities, expression of various features may be encouraged, their synthesis and variations may be achieved to enable a child to experience the nurtured qualities and to develop them. The results of the research on expression of leadership qualities of pre-primary children in musical activities showed that children’s leadership qualities are expressed in singing most frequently. Expression of leadership in other activities such as listening to music, playing and rhythmisation, improvisation and creation, is not so suggestive. Expression of leadership qualities in all activities should be encouraged, whereas during singing activities, all the distinguished leadership qualities were noticed: communicating with adults, generating of ideas, leading of activities and play, initiative, activity, empathy, creativity, curiosity, sensitivity, self-regulation and self-control. The analysis of children’s opinion about leadership qualities revealed that: 1) distribution of favorable musical activities is predetermined by child’s wish to involve in a certain activity and its attractiveness. Therefore, the role of a teacher is important presenting these activities in an attractive way and making attempts to strengthen learners’ interested in them; 2) children like to rally other children for activities but involve in them to a different extent. Some of them seek to lead, others generate ideas and show initiative to rally other children but they later assume the role of a collaborator and do not lead activities. Moreover, a number of children experience a negative influence of their peers, when they are not invited to engage in play, i.e., they lose self-confidence or engage in play only as an observer.